Effective Ministry Structure and Its Impact to Strategic Evangelism - Harwanto, Budi (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Evangelism is a basic task of the church. It is a church function to reach out to the unreached people and equip them to be disciples of Christ. Strategic evangelism (SE) is needed to fulfill this mission. One factor that contributes to evangelism strategically is the effective ministry structure (EMS) of the church. This study examined the effective ministry structure and found a significant relationship as well as predicting strategic evangelism. The literature on both SE and EMS has argued that the ministry structure of the church drives the level of evangelism work strategically. A survey of 431 local mission and conference officers, department directors, and pastors in the East Indonesia Union Conference (EIUC) of Seventh-Day Adventist Church (SDA) was conducted. The study determined the perception of respondents on the extent of SE and EMS. The predictive variable was also considered to determine the contribution of EMS to SE. Implementing descriptive statistics, the finding shows that EMS and SE are very highly practiced. Next, using Pearson’s correlation, the result shows a positive and strong significant correlation between EMS and SE. Lastly, applying simple regression analysis, the result shows that EMS helps predict the SE. The church should be encouraged by this study to implement ministry structure effectively because it will help to increase the performance of SE. Keywords : evangelism, ministry, strategic evangelism, effective ministry structure